Randomized Crossover Trial of 2-Week Ketone Ester Treatment in Patients With Type 2 Diabetes and Heart Failure With Preserved Ejection Fraction - Gopalasingam, Nigopan; Berg-Hansen, Kristoffer; Christensen, Kristian Hylleberg; Ladefoged, Bertil T.; Poulsen, Steen Hvitfeldt; Andersen, Mads Jønsson; Borlaug, Barry A.; Nielsen, Roni; Møller, Niels; Wiggers, Henrik (Circulation (New York, N.Y.), 2024)
BACKGROUND: Heart failure with preserved ejection fraction (HFpEF) is a major cause of morbidity and mortality in patients with type 2 diabetes (T2D). Acute increases in circulating levels of ketone body 3-hydroxybutyrate have beneficial acute hemodynamic effects in patients without T2D with chronic heart failure with reduced ejection fraction. However, the cardiovascular effects of prolonged oral ketone ester (KE) treatment in patients with T2D and HFpEF remain unknown. METHODS: A total of 24 patients with T2D and HFpEF completed a 6-week randomized, double-blind crossover study. All patients received 2 weeks of KE treatment (25 g D-ß-hydroxybutyrate-(R)-1,3-butanediol × 4 daily) and isocaloric and isovolumic placebo, separated by a 2-week washout period. At the end of each treatment period, patients underwent right heart catheterization, echocardiography, and blood samples at trough levels of intervention, and then during a 4-hour resting period after a single dose. A subsequent second dose was administered, followed by an exercise test. The primary end point was cardiac output during the 4-hour rest period. RESULTS: During the 4-hour resting period, circulating 3-hydroxybutyrate levels were 10-fold higher after KE treatment (1010±56 µmol/L; P<0.001) compared with placebo (91±55 µmol/L). Compared with placebo, KE treatment increased cardiac output by 0.2 L/min (95% CI, 0.1 to 0.3) during the 4-hour period and decreased pulmonary capillary wedge pressure at rest by 1 mm Hg (95% CI, -2 to 0) and at peak exercise by 5 mm Hg (95% CI, -9 to -1). KE treatment decreased the pressure-flow relationship (∆ pulmonary capillary wedge pressure/∆ cardiac output) significantly during exercise (P<0.001) and increased stroke volume by 10 mL (95% CI, 0 to 20) at peak exercise. KE right-shifted the left ventricular end-diastolic pressure-volume relationship, suggestive of reduced left ventricular stiffness and improved compliance. Favorable hemodynamic responses of KE treatment were also observed in patients treated with sodium-glucose transporter-2 inhibitors and glucagon-like peptide-1 analogs. CONCLUSIONS: In patients with T2D and HFpEF, a 2-week oral KE treatment increased cardiac output and reduced cardiac filling pressures and ventricular stiffness. At peak exercise, KE treatment markedly decreased pulmonary capillary wedge pressure and improved pressure-flow relationship. Modulation of circulating ketone levels is a potential new treatment modality for patients with T2D and HFpEF. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique Identifier: NCT05236335.